Knockdown of RREB1 inhibits cell proliferation via enhanced p16 expression in gastric cancer. Issue 23 (2nd December 2021) - Gao, Qi; Wu, Yunhua; Lu, Chaoxiang; Kai, Wang; Xie, Weike; Wang, Qi; Wang, Lei; Liu, Shiqi; Pan, Yongkang
ABSTRACT: Gastric cancer (GC) is the most common gastrointestinal malignancy worldwide. However, the molecular mechanisms of the progression of GC are not fully understood. Ras-responsive element binding protein 1 (RREB1) is an oncogene in many types of cancer that is involved in various biological processes, such as DNA damage repair, cell growth and proliferation, cell differentiation, fat development, and fasting glucose balance. In this study, we demonstrate the role of RREB1 in gastric cancer. First, by immunohistochemistry staining (IHC) and bioinformatics analysis, we demonstrated the expression of RREB1 in gastric cancer and paired normal gastric tissues. Then, we established RREB1 overexpression and knockdown cell lines via lentiviral transfection and detected cell proliferation by using MTT, colony-forming, cell cycle and apoptosis assays in vitro. We demonstrated the effect of RREB1 on cell proliferation in vivo by using a subcutaneous xenograft tumor model in nude mice. Finally, by using Western blotting and IHC, we demonstrated the possible mechanism by which RREB1 affects cell proliferation. The IHC and bioinformatics analyses demonstrated that RREB1 was highly expressed in gastric cancer and showed that RREB1-expressing patients had a larger tumor size and more lymphovascular invasion than RREB1-negative patients. Knockdown of RREB1 inhibited cell proliferation in vivo and in vitro. Knockdown of RREB1 enhanced p16 expression in vivo and in vitro, and p16 expression was negatively related to RREB1 in gastric cancer tissue. RREB1 was highly expressed in gastric cancer, and knockdown of RREB1 inhibited cell proliferation via enhanced p16 expression.